Food insecurity and level of depression among patients with chronic diseases, and associated factors during the COVID-19 lockdown: a cross-sectional study in rural Rwanda. Issue 10 (10th October 2022) - Umutoniwase, Sabine; Nshimyiryo, Alphonse; Barnhart, Dale A; Dusabeyezu, Symaque; Mpanumusingo, Egide; Nahimana, Evrard; Mubiligi, Joel M.; Cubaka, Vincent K
Abstract : Objectives: We aimed to describe access to food and symptoms of depression among patients with chronic diseases or their caregivers, and assess associated factors during the COVID-19 lockdown in rural Rwanda. Design: A cross-sectional study. Setting and participants: A stratified random sampling technique was used to recruit 220 patients enrolled in the HIV, non-communicable diseases, mental health, paediatric development clinic and oncology programmes in three rural districts of Rwanda. Outcome measures: Telephone-based interviews were conducted to collect data on the number of daily meals before and during the COVID-19, and depression was assessed using the Patient Health Questionnaire-9. We used logistic regression analysis to investigate factors associated with households reporting a reduction in daily meals and with the survey respondent reporting symptoms of depression. Results: Of the participants, 19.1% reported a reduction in daily number of meals for either adults or children in their households during lockdown and 24.6% had depression. Reporting a reduction in daily meals was associated with the district of residence and estimated household's monthly income. Self-reported depression was significantly associated with negative experiences during lockdown, including reporting feeling depressed or fear (AOR 4.82; 95% CI 2.08 to 11.21), loneliness (AOR 4.33; 95% CI 1.32 to 14.13), reduction in daily meals (AOR 4.15; 95% CI 1.56 to 11.00) and lack of access to healthcare (OR 3.29; 95% CI 1.32 to 8.23). Conclusions: Our findings suggest that significant reduction in access to food affected rural Rwandans with chronic diseases during COVID-19 lockdown, and the lockdown effect varied by household's pre-pandemic level of vulnerability to food insecurity. Reduction in household meals, as well as other self-reported effects of the lockdown, were associated with worse psychological status of survey respondents. Economic and food support should be considered by governments and non-governmental organisations to protect those most vulnerable including patients with chronic diseases against the effects of pandemics and their associated containment measures.